A fluorescent sensor based on oyster mushroom-carbon dots for sensing nitroarenes in aqueous solutions. (11th June 2020) - Zulfajri, Muhammad; Rasool, Akhtar; Huang, Genin Gary
Abstract : The synthesis of OM-CDs and their sensing application for NAs. Abstract : Contamination of nitroarenes (NAs) seriously endangers the environment and the health of organisms. Therefore, the development of a fluorescent sensor with good response for sensing NAs is crucial. Herein, eco-friendly carbon dots (CDs) from oyster mushroom (OM) as a sole carbon precursor were effectively produced via a facile hydrothermal treatment method. The properties of the OM-CDs were evaluated via TEM, FT-IR spectroscopy, Raman spectroscopy, UV-light, fluorescence spectroscopy, and UV-Vis spectroscopy. The OM-CDs possessed mono-dispersed spherical forms with a narrow size distribution. The OM-CDs also exhibited a cyan color excited by a 360 nm excitation wavelength with a 12.51% quantum yield. The fluorescent behavior of the OM-CDs was found to be dependent on the excitation wavelength, and they were used as a rapid and sensitive fluorescent sensor for NAs with broad linear responses and low detection limits. The NAs quenched the fluorescence emission intensity of the OM-CDs because of the inner filter effect (IFE), fluorescence resonance energy transfer (FRET), and photo-induced electron transfer (PET), which conferred the sensing mechanisms. The absorbance spectra of o -NA and p -NA have a wider overlap with the fluorescence excitation and emission spectra of OM-CDs than those of m -NA and p -NP, resulting in higher quenching efficiency of o -NA and p -NA. Eventually, this fluorescent sensor presented practicability to determine NAs in real water samples. The successful determinations of these NAs in the underground water samples were performed with RSDs below 2% and spiked recoveries between 97.20% and 102.60%.